STRATEGI KONTEN VISUAL DALAM PENYAJIAN MATERI PELATIHAN KEPEGAWAIAN DI KEMENTERIAN KESEHATAN - Haqqi, Muhammad; Tri Harpin Pranata, Rici; Marithasari, Harries (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Advances in digital technology are driving changes in the delivery of information and training materials, including within the government sector. Visual content has become an important communication strategy for enhancing the effectiveness of material delivery, making it more engaging, communicative, and easy to understand. This study aims to analyze visual content strategies in the presentation of civil service training materials at the Center for Civil Service Competency Development (P2KA) of the Ministry of Health. The method used in this study is a qualitative method employing a descriptive approach. Data were collected through participatory observation, semi-structured interviews, and documentation of the visual material development process within the P2KA environment. The results indicate that visual content strategies at P2KA are implemented through three main stages: planning, production, and team collaboration. The planning process involves evaluation, research, and coordination between content developers and visual designers. Content production utilizes various visual media such as presentations, infographics, posters, booklets, and animated videos. Additionally, supportive team collaboration contributes to the effectiveness of material production. The use of visual content has proven to enhance participants’ understanding of training materials. However, further strengthening is needed in the areas of visual standardization, team integration, and more measurable effectiveness evaluation to ensure the visual content can perform more effectively and sustainably.